SLEEPING TREE PREFERENCE OF SIAMANG IN THE BUFFER ZONE OF DOLOK SIBUAL-BUALI NATURE RESERVE - Abdul Haris Mustari; Meylia, Safira Arda; Burhanuddin Masy'ud (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
Sleeping trees are one of the important components in the siamang habitat as an arboreal primate. The purpose of this study was to analyze the characteristics and preferences of the siamang sleeping tree and the parameters that influence it. This research was conducted in the buffer zone of the Dolok Sibual-buali Nature Reserve, North Sumatra from April to May 2022. Data collection was carried out by direct observation, recording, and measurement. The characteristics of the siamang sleeping tree generally include three parameters, namely biotic, physical, and anthropogenic activity factors. There are 12 species of trees identified as siamang sleeping trees. Based on the results of PCA, obtained 6 parameters that have the most influence on the selection of siamang sleeping trees, namely activity from cultivated land, the canopy vertical length, NDVI, distance from feeding plants, distance from settlements, and slope direction. Siamang in habitats that intersect with anthropogenic activity based on the Neu index tends to prefer the location of sleeping trees with a distance of 222,9 – 268,71 m from cultivated land and 1573,5 – 1904,29 m from settlements. Key words: Characteristics, preference, sleeping tree, siamang